Potensi Antioksidan Rumput Kebar (Biophytum Umbraculum) dengan Metode 2.2-Diphenyl-1-Picrylhydrazyl (DPPH) dan Ferric Reducing Antioxidant Power (FRAP) - Fri Rahmawati; Maria Bintang; Albert Jackson Yang; Hazella Ishera Talakua (Pro-Life, 2025)
Oxidative stress is one of the causes of heart disease, atherosclerosis, and cancer. Efforts to overcome oxidative stress include the use of natural antioxidants. Flavonoids and phenolics are secondary metabolite compounds in plants that have antioxidant activity. Plants that are believed to be able to overcome oxidative stress include Kebar grass. Kebar grass (Biophytum umbraculum) is one of the plants that empirically has many benefits including as a female fertility drug by the Kebar-Papua community. The study aimed to determine the antioxidant potential and total phenolic and flavonoid content of Kebar grass extract. Kebar grass extract was obtained through maceration extraction with 96% pro-analysis (p.a) ethanol solvent. Antioxidant testing used the 2.2-diphenyll-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) methods using antioxidant standards, namely ascorbic acid (vitamin C) and gallic acid, while measuring total phenolic and flavonoid levels used the Folin-Ciocalteu and aluminium chloride methods, respectively. The results showed that the total phenolic and flavonoid levels of Kebar grass extract were 52.26 ± 3.94 mg GAE/g dw (dry weight) and 22.15 ± 2.79 mg QE/g dw Kebar grass extract, respectively, while the antioxidants of Kebar grass extract with the DPPH method had an inhibition concentration 50 (IC50) value of 183.44 ppm and a vitamin C standard of 4.46 ppm, and antioxidant testing using the FRAP method obtained a reducing power 50 (RP50) value of Kebar grass extract of 5043.76 ppm with a gallic acid standard value of 101.8 ppm.